2005
DOI: 10.1007/s00280-005-0125-1
|View full text |Cite
|
Sign up to set email alerts
|

A phase I clinical trial of 12- O-tetradecanoylphorbol-13-acetate for patients with relapsed/refractory malignancies

Abstract: Phorbol esters activate protein kinase C and modulate a variety of downstream cell signaling pathways. 12-O-tetradecanoylphorbol-13-acetate (TPA) is a phorbol ester that induces differentiation or apoptosis in a variety of cell lines at low concentrations. A phase I dose escalation trial of TPA was undertaken for patients with relapsed or refractory malignancies. The starting dose was 0.063 mg/m2 and most patients were treated with an intravenous infusion of TPA on days 1-5 and 8-12 followed by a 2-week rest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
1
37
0
1
Order By: Relevance
“…infusions of TPA increased the number of circulating WBC and neutrophils in patients with depressed bone marrow caused by prior treatment with cytotoxic chemotherapeutic drugs (2). The results obtained in both studies and data from a phase I trial with TPA at the Cancer Institute of New Jersey in New Brunswick (3,4) indicated an acceptable toxicity profile. In cell culture studies, a low clinically achievable concentration of TPA (0.16 nmol/L) in combination with clinically achievable concentrations of all-trans retinoic acid (0.1-1 Amol/L), 1a,25-dihydroxyvitamin D 3 (1 nmol/L), or sodium butyrate (100 Amol/L) synergistically inhibited the growth and stimulated the differentiation of cultured HL-60 myeloid leukemia cells, suggesting that combinations of these drugs may be more effective than TPA alone for the treatment of refractory myeloid leukemia patients (5).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…infusions of TPA increased the number of circulating WBC and neutrophils in patients with depressed bone marrow caused by prior treatment with cytotoxic chemotherapeutic drugs (2). The results obtained in both studies and data from a phase I trial with TPA at the Cancer Institute of New Jersey in New Brunswick (3,4) indicated an acceptable toxicity profile. In cell culture studies, a low clinically achievable concentration of TPA (0.16 nmol/L) in combination with clinically achievable concentrations of all-trans retinoic acid (0.1-1 Amol/L), 1a,25-dihydroxyvitamin D 3 (1 nmol/L), or sodium butyrate (100 Amol/L) synergistically inhibited the growth and stimulated the differentiation of cultured HL-60 myeloid leukemia cells, suggesting that combinations of these drugs may be more effective than TPA alone for the treatment of refractory myeloid leukemia patients (5).…”
mentioning
confidence: 53%
“…Our earlier study showed that the peak blood concentrations of TPA F SD in several patients who received an i.v. infusion of TPA (0.125 mg/m 2 ) was 1.75 F 0.55 ng/mL and ranged between 0.3 and 5.2 ng/mL (4,23). Our recent study showed that the peak blood level of TPA after a 100 ng/g body weight injection was f1 ng/mL (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Therefore, accurately knowing the interaction forces between cells and cell-proteins would allow better comprehension of the potential therapeutic effect of drug candidates. 44 However, many agents, such as the PMA studied here, which was used in clinical trials for hematologic malignancy, 45,46 are activators in the signaling transduction pathway of PKC, 47 which can affect not only the adhesion and migration behavior of cells but also their proliferation, differentiation, and death. For such agents, the conventional batch-cell adhesion assays (such as that shown in Figure 1), may not give a precise indication of the intrinsic cell adhesion and hence metastatic potential, since cell proliferation is also affected by the treatment and the cell adhesion may be affected by the trypsinization.…”
mentioning
confidence: 99%
“…However, difficulties are associated with their application to therapeutic uses due to their potent tumor-promoting and inflammatory activities. 7,8) Bryostatin-1 (bryo-1) 9) which was isolated from the marine bryozoan Bugula neritina, is a unique PKC activator that does not exhibit tumor-promoting or inflammatory activity. Bryo-1 has been reported to have significant anti-cancer and anti-proliferative activities, and these have been attributed to activation of the PKCδ isozyme, [10][11][12] which plays a tumor suppressor role and is involved in apoptosis.…”
mentioning
confidence: 99%